Optimasi Upah Dan Tenaga Kerja Pada Proyek Perumahan Graha Famili Surabaya: Wage And Employment Optimization In The Graha Famili Surabaya Housing Project - Diah Listyaningsih; Anton Sulistiawan; Mohamad Ferdaus Noor Aulady (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Linear programming can be an alternative in solving problems in the construction sector. In construction work there is a workforce, but the allocation of the number of workers used requires good planning. If the allocation of the number of the worker is optimal, then the costs incurred for labor wages are also more efficient. For this reason, this study aims to optimize wages and the number of workers in construction projects. In performing optimization, the method used is simplex analysis. The simplex method is a linier program that can be used more than 3 variables, to solve the problem by iterating or recalculation until it reaches the optimal solution. The results of this are a decrease in the cost of labor wages, for concrete work there is a decrease in the cost of labor wages by 8,60%, and ceiling work there is a decrease in the cost of labor wages by 58,59%.